ijee 2022
DOI: 10.48165/ijee.2022.58328
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Acuity on Climate Change in the Central Dry Zone of Karnataka

Abstract: To counteract the vulnerability results from climate change, it is critical to understand farmers’ viewpoints. In Karnataka, farmers’ perspectives, implications, adaptive measures, and barriers were investigated during 2021 by collecting the data from farmers using multistage random sample technique. Farmers witnessed significant changes in temperature, rainfall distribution, emergence of new plant pests and infirmity over time as a result of the introduction of new cultivars/crops, and the occurrence of droug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…The findings of present study have a similarity with the results reported by Sarkar et al, (2022). Narayanan andSahu (2016) &Ashoka et al, (2022) Note: Low (upto 2.5 acre), Medium (>2.5-5 acre), High (>5-10 acre)…”
Section: Resultssupporting
confidence: 92%
“…The findings of present study have a similarity with the results reported by Sarkar et al, (2022). Narayanan andSahu (2016) &Ashoka et al, (2022) Note: Low (upto 2.5 acre), Medium (>2.5-5 acre), High (>5-10 acre)…”
Section: Resultssupporting
confidence: 92%
“…Climate change and extreme hazards like floods and severe droughts lead to substantial crop losses, volatility of food prices, and livelihood insecurity (Ghanghas et al, 2015;Meena et al, 2022). Climate change has a variety of effects on agriculture, including decreased crop productivity, incidence of pest and diseases and change in cropping pattern (Ashoka et al, 2022). Climate change has also become a global issue requiring attention and action because to increasing temperatures, extensive glacier melt, variations in the increased frequency of catastrophic events, and more (Pabba et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, agriculture and food security has influenced the impact of temperature change and livelihoods of huge sections of the urban and rural populations globally. India being a developing country with diverse agro-climatic regions, challenging geographies, growing economies, diverse agricultural cultivation systems and farm typologies is more prone to the consequence of temperature change because of more dependence on agriculture for livelihood (Ashoka et al, 2022). Adaptation, a complex, multidimensional, and multi-scale process, and defined as adjustments to behaviour or economic structures that reduce vulnerability of society within the face of scarcity or threatening environmental change (Adger et al, 2003).…”
Section: Introductionmentioning
confidence: 99%